التفاعل اللفظي وفق أداة (فلاندرز) وأثره في عملية التدريس بمدارس التعليم الأساسي بسلطنة عمان - Ali Hassan Al-Balushi; Kirembwe Rashid Abdul Hamed (Usuli Faqih Research Centre PLT, 2024)
Non-Indexed Publication